PROXIMITY SENSOR - WAKI NAOZUMI; KAWASAKI YUYA (2018)
PROBLEM TO BE SOLVED: To improve detection accuracy of a proximity degree of an article.SOLUTION: A proximity sensor receives reflection light reaching by reflecting light-emission pulses to an article, and detects proximity of the article. The proximity sensor comprises: a conversion circuit for converting a current outputted from a light receiving element receiving the reflection light with a magnitude according to a proximity degree of the article, and outputting it; a differential conversion circuit for converting an output voltage of the conversion circuit to a differential voltage, and outputting it; and a correlation double sampling circuit with a differential constitution for subtracting a value obtained by sampling an output differential voltage of the differential conversion circuit with a fall of the light emission pulses from a value obtained by sampling the output differential voltage in the differential conversion circuit with a rise of the light-emission pulses.SELECTED DRAWING: Figure 1 【課題】物体の近接度合いの検出精度の向上。【解決手段】発光パルスが物体に反射することにより到来する反射光を受光し、前記物体の近接を検出する近接センサであって、前記反射光を受光する受光素子から前記物体の近接度合いに応じた大きさで出力される電流を、電圧に変換して出力する変換回路と、前記変換回路の出力電圧を差動電圧に変換して出力する差動変換回路と、前記差動変換回路の出力差動電圧を前記発光パルスの立ち上がりでサンプリングした値から、前記出力差動電圧を前記発光パルスの立ち下がりでサンプリングした値を減算する、差動構成の相関二重サンプリング回路とを備える、近接センサ。【選択図】図１